A Study on the Competitiveness of Group-Based Enterprises in “Desa Mandiri Anggur Merah” on Sumba Island, East Nusa Tenggara Province - Christiana Wahyuningrum; Thomas Ola Langoday; Marius Masri; M. E. Perseveranda; Agustina Sadri Yathy Lay (Asian Journal of Management Analytics, 2026)
This study examines the competitiveness of group-based enterprises in Desa Mandiri Anggur Merah in the Sumba Region, East Nusa Tenggara Province, Indonesia. Shift Share Analysis and the Location Quotient (LQ) method were applied to identify leading commodities among group enterprises. The findings indicate that the Sumba region has comparative advantages primarily in the livestock sector and food crop production. Livestock enterprise groups are predominantly concentrated in East Sumba, where cattle farming demonstrates high competitiveness, and Southwest Sumba, where pig farming emerges as the leading commodity. In 2012, East Sumba recorded the highest number of livestock groups (203 groups), followed by Southwest Sumba (94 groups), West Sumba (44 groups), and Central Sumba (22 groups). Based on empirical evidence and analytical results, a cluster-based development approach is proposed.